2019
DOI: 10.37897/rjp.2019.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Psychological disturbances in adolescents with acute voluntary poisoning

Abstract: Objective. The present study has two main objectives: to evaluate the psychological characteristics of adolescents with voluntary acute poisoning in a pediatric toxicology department and to estimate the role of psychological evaluation in the management of these patients. Material and method. The study includes the retrospective analysis of all patients with voluntary acute intoxication, admitted to our clinic between October 1, 2017 and September 30, 2018. The following criteria were considered: age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Compared to the accidental group in the current study, the suicidal poisoning group had a significant association with a history of psychiatric illness (19.4% versus 5.3%, p = 0.033) and therapeutic psychiatric drug administration (16.2% versus 2.6%, p = 0.027). These findings are harmonious with the results of previous researchers [34,35] who revealed that 13% and 31.6% of suicidal poisoned patients, respectively, had pre-existing psychiatric disorders. Nistor and colleagues [36] also concluded that psychological disturbance increases the risk of suicidal poisoning by 11% to 27% more than the overall population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to the accidental group in the current study, the suicidal poisoning group had a significant association with a history of psychiatric illness (19.4% versus 5.3%, p = 0.033) and therapeutic psychiatric drug administration (16.2% versus 2.6%, p = 0.027). These findings are harmonious with the results of previous researchers [34,35] who revealed that 13% and 31.6% of suicidal poisoned patients, respectively, had pre-existing psychiatric disorders. Nistor and colleagues [36] also concluded that psychological disturbance increases the risk of suicidal poisoning by 11% to 27% more than the overall population.…”
Section: Discussionsupporting
confidence: 91%
“…This result was in concurrence with Dedic and colleagues [ 53 ], who recorded that the HAM-D scores were moderate-to-severe in suicidal poisoning subjects, while mild in controls. Furthermore, Nitescu and colleagues [ 34 ] noticed that depression represented 36.1% of common psychiatric disorders among adolescents with suicidal poisoning. Similarly, a previous research in China [ 54 ] concluded that more than half of their included subjects had moderate-to-severe degrees of both anxiety and depression during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%